Rancang Bangun Standard Operating Procedure Preservasi Koleksi Tercetak Di Perpustakaan - Nabila, Jeihan (Universitas Negeri Padang, 2020)
A good library management is very much determined by a system built in the library. One of the subsystems that has to come into attention is the Standard Operating Procedure (SOP). With a well-developed SOP (valid, systematic, and clear), a library can operate well in supporting the works of the librarians. One of the most important SOPs in the works of library is the preservation SOP. A good preservation SOP is a standard which can be used by all libraries nationwide. This research is aimed at producing a preventive preservation SOP to prevent biota damage in the forms of flowchart. This research was conducted at Dispusipda library, UPT LIPI library and Goethe-Institute library. Methods used in this research is action research due to implementative actions at some libraries. This research produces a design of SOP on preservation part on printed collections which function as working guidance to lay down work procedure on an SOP guidance and decreasing errors by the librarians, to improve work effiency and quality of the libraries. This SOP design is made to meet three parts involved in maintenance of printed collections, from preventive care to curative repairment actions on printed collections. According to these three flows, an SOP design is made with main SOP, preservation SOP for biota prevention.